Word production in children with cochlear implant based on chronological age and hearing age Hör- und Lebensalter-bezogene Wortproduktion von Kindern mit Cochlea-Implantat - Glaubitz, Cynthia; Geiss, Katrin T.; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2022)
Background For congenitally deaf children, an early bilateral provision with cochlear implant (CI) is a favourable condition for language acquisition. The objective of the present study was to determine the word production in CI children. The focus was on a comparison of chronological age and hearing age performance and on the evaluation of potential effects of multilingualism, additional disabilities and age at provision. Methods The data of 62 children with bilateral CI (age at provision in months M= 12,1; SD = 6,2) were retrospectively analysed. Vocabulary was assessed by the test Aktiver Wortschatztest für 3- bis 5-jährige Kinder – Revision and compared for chronological age and hearing age. Group comparisons and correlation analysis was conducted regarding multilingualism, additional disabilities and age at provision. Results The cohort performed significantly better when referenced o hearing age: level were within or above the norm in more than 50 %; referenced to chronological age in around 37 %. The descriptive performance differences for multilingualism and additional disabilities were only significant for children with both characteristics. Performance of monolingual children without additional disabilities was not significantly associated with age at provision. Conclusion CI children may achieve an adequate expressive vocabulary at the age of 3 to 5 years. Multilingualism and additional disabilities seem to be particular challenges for CI children and need a more precise definition in further studies. The use of both chronological and hearing age as reference marks allows a differentiated assessment of the language status. This may lead to benefits in therapeutic interventions and parent councelling.
CRIS-Team Scopus Importer:2022-09-30
Keywords: AWST-R; Cochlea-Implantation; expressive Sprache; Höralter; Mehrsprachigkeit; Sprachdiagnostik; Sprachentwicklung; Sprachproduktion; Wortschatz; Zusatzbeeinträchtigung